The Effect of Training Program Using Small – Sided Games on The Improvement of Passing and Scoring in Female Futsal Players - Alhayali, Roaa; Khalif, Emad (Journal of Physical Education, 2022)
The research aimed at designing exercises according to small – sided games for passing and scoring in female futsal players as well as identifying their effect on the development of passing and scoring in female futsal players. The researchers used the experimental method on (28) Al Zewraa futsal player and Bladi futsal players. The training program was applied using S.S.G on experimental group players for 8 weeks with 3 training sessions per week. The results showed significant improvement in posttests results in favor of the experimental group that followed the small – sided games in passing and scoring tests.